Effect of various types of propagation on the yield of wine blackberries (Rubus adenotrichus). - Orozco-Rodríguez, Rafael (2011)
This research project was intended to determine the effect of two different systems of propagation—macropropagation and micropropagation—on yield of two varieties of blackberries (Rubusadenotrichus): “Re d Thorn-Wine” and “Thornless Wine.”This experiment was carried out in 2005 at La Luchita, in El Guarco, Cartago, Costa Rica. The harvest took place duringthe years 2007 and 2008. Significant differences were found(P=0,0034) between the systems for propagation of the “Red-Thorn Wine” variety, in 2007. The plants resulting from macropropagation showed the higher production average.The production for the “Thornless Wine” variety was null that year. In 2008 there were no significant differences found(P>0,6207) between the two propagation systems for eitherone of the varieties. When compared, “Red-Thorn Wine” variety showed a higher production under the two propagation systems (P<0,00183).